The Effect of Combined Exercise Training on Tumor Necrosis Factor-Alpha, Eotaxin-1, Atherogenic Indices, and Muscle Strength of Obese Elderly Men - Mina Safari; Ramin Shabani; Alireza Elmieh (مجله علوم پزشکی صدرا)
Introduction: The prevalence of obesity among elderly populations continues to rise. Exercise training may reduce chronic inflammation by modulating pro-inflammatory cytokine levels. This study aimed to investigate the effects of combined exercise training on the expression of tumor necrosis factor-alpha (TNF-α), eotaxin-1, atherogenic indices, and muscle strength in obese elderly men.Methods: In this semi-experimental study, 40 obese elderly men (mean age 61.90±2.84 years) were randomly assigned to either an experimental or control group. The experimental group completed 16 weeks of progressive combined exercise training (3 sessions per week, 90 minutes each session). Plasma levels of TNF-α, eotaxin-1, atherogenic indices, and muscle strength were measured 48 hours before and after the intervention. Data were analyzed using independent and paired t-tests in SPSS software version 26. P<0.05 was considered statistically significant.Results: The experimental group demonstrated significant reductions in TNF-α (P=0.0001), eotaxin-1 (P=0.0001), and atherogenic indices (P=0.009), along with increased fat-free mass (P=0.03) compared to controls. The paired t-test results in the experimental group also demonstrated similar significant changes in the aforementioned factors (P<0.05).Conclusion: The results indicated that combined training effectively reduced levels of TNF-α, eotaxin-1, and atherogenic indicators while increasing lower-body muscle strength in obese elderly men.IRCT registration number: IRCT20200509047372N1.